Ultrafine Pt nanoparticle decoration with CoP as highly active electrocatalyst for alcohol oxidation. Issue 102 (21st October 2016) - Xiao, Xin; Huang, Dekang; Luo, Yanping; Li, Man; Wang, Mingkui; Shen, Yan
Abstract : Ultrafine Pt nanoparticles decorated with CoP provide a promising bifunctional electrocatalyst for alcohol oxidation. Abstract : Improving the catalytic activity and stability of Pt-based electrocatalysts for the oxidation of alcohols is essential for their commercialization. In this study, CoP was introduced as a catalytic promoter material for Pt nanoparticles, to produce bifunctional catalysts for the oxidation of methanol and ethanol. The Pt–CoP/C-30% electrode shows current densities of 1300 mA mgPt −1 for methanol oxidation and 857 mA mgPt −1 for ethanol oxidation, which significantly overwhelm those of the commercially available Pt/C catalyst (current densities of 291 mA mgPt −1 for methanol oxidation and 346 mA mgPt −1 for ethanol oxidation, respectively). The bifunctional mechanism and electronic effect caused by the addition of CoP contribute to the excellent performance of Pt–CoP/C-30%. We conclude that Pt–CoP/C-30% can serve as an effective electrocatalyst for next generation high-performance fuel cells.